Fluorescent Membrane Tension Probes for Early Endosomes. Issue 22 (26th April 2021) - Piazzolla, Francesca; Mercier, Vincent; Assies, Lea; Sakai, Naomi; Roux, Aurelien; Matile, Stefan
Abstract: Fluorescent flipper probes have been introduced recently to image membrane tension in live cells, and strategies to target these probes to specific membranes are emerging. In this context, early endosome (EE) targeting without the use of protein engineering is especially appealing because it translates into a fascinating transport problem. Weakly basic probes, commonly used to track the inside of acidic late endosomes and lysosomes, are poorly retained in EE because they are sufficiently neutralized in weakly acidic EE, thus able to diffuse out. Here, we disclose a rational strategy to target EE using a substituted benzylamine with a higher p K a value as a head group of the flipper probe. The resulting EE flippers are validated for preserved mechanosensitivity, ready for use in biology, particularly to elucidate the mechanics of endocytosis. Abstract : Unidirectional penetration along minimalist pH gradients is developed as a strategy to label the membrane of early endosomes with mechanosensitive flipper probes, by simple addition to unmodified cells. Substituted benzylamines offer the right acidity, p K a =10, not too strong to allow reversibility, not too weak to inhibit penetration from neutral water in the cytosol, and, perhaps, extra returns from interfacial aromatic anchoring.